Computational investigation of left ventricular hemodynamics following bioprosthetic aortic and mitral valve replacement. (March 2021) - Xu, Fei; Johnson, Emily L.; Wang, Chenglong; Jafari, Arian; Yang, Cheng-Hau; Sacks, Michael S.; Krishnamurthy, Adarsh; Hsu, Ming-Chen
Highlights: FSI framework for a left ventricle with two bioprosthetic implants is proposed. Hemodynamics of left ventricle and structural mechanics of valve implants are modeled. Replacing native mitral valve with tri-radially symmetric valve changes hemodynamics. Abstract: The left ventricle of the heart is a fundamental structure in the human cardiac system that pumps oxygenated blood into the systemic circulation. Several valvular conditions can cause the aortic and mitral valves associated with the left ventricle to become severely diseased and require replacement. However, the clinical outcomes of such operations, specifically the postoperative ventricular hemodynamics of replacing both valves, are not well understood. This work uses computational fluid–structure interaction (FSI) to develop an improved understanding of this effect by modeling a left ventricle with the aortic and mitral valves replaced with bioprostheses. We use a hybrid Arbitrary Lagrangian–Eulerian/immersogeometric framework to accommodate the analysis of cardiac hemodynamics and heart valve structural mechanics in a moving fluid domain. The motion of the endocardium is obtained from a cardiac biomechanics simulation and provided as an input to the proposed numerical framework. The results from the simulations in this work indicate that the replacement of the native mitral valve with a tri-radially symmetric bioprosthesis dramatically changes the ventricular hemodynamics. Most significantly, the vortical motion in the left ventricle is found to reverse direction after mitral valve replacement. This study demonstrates that the proposed computational FSI framework is capable of simulating complex multiphysics problems and can provide an in-depth understanding of the cardiac mechanics.